2023
DOI: 10.3390/genes14020399
|View full text |Cite
|
Sign up to set email alerts
|

Global Distribution of Founder Variants Associated with Non-Syndromic Hearing Impairment

Abstract: The genetic etiology of non-syndromic hearing impairment (NSHI) is highly heterogeneous with over 124 distinct genes identified. The wide spectrum of implicated genes has challenged the implementation of molecular diagnosis with equal clinical validity in all settings. Differential frequencies of allelic variants in the most common NSHI causal gene, gap junction beta 2 (GJB2), has been described as stemming from the segregation of a founder variant and/or spontaneous germline variant hot spots. We aimed to sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 109 publications
0
7
0
2
Order By: Relevance
“…The reported differences in the FMD prevalence may be due to differences in the genetic structure of each population. More frequent and founder variants in hearing impairment genes have already been described in European, African, Asian, and American populations (Aboagye et al 2023 ; Adadey et al 2022 ); therefore, finding founder variants in specific genes that cause FMD would not be surprising. Founder variants are those variants found with a high frequency within a particular population caused by the presence of the variant in an ancestor or small group of ancestors (Jain et al 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The reported differences in the FMD prevalence may be due to differences in the genetic structure of each population. More frequent and founder variants in hearing impairment genes have already been described in European, African, Asian, and American populations (Aboagye et al 2023 ; Adadey et al 2022 ); therefore, finding founder variants in specific genes that cause FMD would not be surprising. Founder variants are those variants found with a high frequency within a particular population caused by the presence of the variant in an ancestor or small group of ancestors (Jain et al 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that several non-syndromic SNHL genes have a founder effect in the Asian population (48 variants in 14 genes, 85.7%). However, there are few reported genes showing founder variants in the European population [9 variants in GJB2 [OMIM 121,011), TMC1 (OMIM 606,706) , and TMIE (OMIM 607,237) genes] (Aboagye et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reported differences in the FMD prevalence may be due to differences in the genetic structure of each population. More frequent and founder variants in hearing impairment genes have already been described in European, African, Asian, and American populations (14,35), therefore, nding founder variants in speci c genes that cause FMD would not be surprising. Founder variants are those pathogenic variants found with a high frequency within a particular population caused by the presence of the variant in an ancestor or small group of ancestors (36).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that several non-syndromic SNHL genes have a founder effect in the Asian population (48 variants in 14 genes, 85.7%). However, there are few genes reported showing founder variants in the European population (9 variants in GJB2 (OMIM: 121011), TMC1 (OMIM: 606706), and TMIE (OMIM: 607237) genes) (14).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss is one of the most significant hereditary heterogeneous diseases 4,5 present in at least 1 out of every 500 newborns worldwide 6 ; up to 60% of these cases have a genetic aetiology 7,8 . During the past two decades, tremendous progress has been made in the identification of causative genes in hereditary nonsyndromic hearing loss, or NSHL 9,10 . To date, a total of 124 NSHL genes have been identified, estimating 51 autosomal dominant (deafness autosomal dominant; DFNA) genes; 77 autosomal recessives (deafness autosomal recessive; DFNB) genes and 5 X‐linked (deafness X‐linked; DFNX; http://hereditaryhearingloss.org/) genes.…”
Section: Introductionmentioning
confidence: 99%